2018
DOI: 10.1002/adem.201701019
|View full text |Cite
|
Sign up to set email alerts
|

Development of Surface‐Engineered Tape‐Casting Method for Fabricating Freestanding Carbon Nanotube Sheets Containing Fe2O3 Nanoparticles for Flexible Batteries

Abstract: Chemical vapor deposition and filtration are commonly used to fabricate freestanding multiwalled carbon nanotube sheets containing iron(III) oxide (Fe 2 O 3 ) (MWCNT-Fe 2 O 3 sheets). However, the former is relatively expensive, and the latter suffers from poor scalability. Here, the authors develop an inexpensive, scalable, high-throughput, tunable tape-casting method for fabricating flexible, foldable freestanding MWCNT-Fe 2 O 3 sheets. When tested as electrodes in lithium-ion batteries, the sheets perform b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 46 publications
(49 reference statements)
0
7
0
1
Order By: Relevance
“…Previously, we have reported MWCNT sheet with matt surface appearance (referred to as matt MWCNT sheet), which was made using industrially compatible roll-to-roll surface-engineered tape-cast (SETC) technique [15][16][17].…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we have reported MWCNT sheet with matt surface appearance (referred to as matt MWCNT sheet), which was made using industrially compatible roll-to-roll surface-engineered tape-cast (SETC) technique [15][16][17].…”
Section: Resultsmentioning
confidence: 99%
“…The solution was exposed to ultrasonication and mechanical stirring with a VCX 750 Ultrasonic Processor (Sonic, USA) and Advanced Hotplate Stirrer (VWR, USA) for 2 min at 500 rpm and 8 min at 800 rpm while the amplitude of sonicator was set at 40%. Then the mixture was tape-casted on top of copper foil (matt-side facing up) 3032 with 5 mm gap and dried in a convection oven (Binder Forced Convection Oven FD 53) at a temperature of 120 °C for 1 hour. After drying, the composite sheet was peeled off from copper sheet and cut into small pieces.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Figure 1 illustrates our processing method for fabrication of PVDF-MWCNT filaments for FFF. The first steps involve the mixing of PVDF powders and MWCNT flakes; and convert them to paper shape using Surface-Engineered Tape-Cast (SETC) technique 3032 . We found that reported approach in the literature (called solution-cast) resulted in the uniform composition of PVDF-MWCNT, but was limited to ~15 wt% CNT due to high viscosity limitation during the solution-cast process 3 .…”
Section: Introductionmentioning
confidence: 99%
“…崔屹课题组 [40] 还将Si与CNT集 合成一个整体, 制备了自支撑的CNT-Si薄膜, 其结构 类似于钢筋增强的混凝土, CNT网络即提供机械支撑, 又发挥导电作用, 而Si作为活性材料, 提供电化学容 量. 抽滤法是制备CNT柔性电极常用的方法 [41~43] , 此 外, 还有一些柔性电极的制备方法被报道, 如流延 法 [44] 、喷雾干燥法 [45] 、蒸发诱导自组装 [46] 等. 除了利用电极本身的弯折能力和多孔结构缓冲 变形应力以外, 一些特殊的电极形态也被设计出来, 控制应力.…”
Section: 一维(1d)、二维(2d)材料由于其特殊的结构与其unclassified